2007
DOI: 10.1179/174328907x177617
|View full text |Cite
|
Sign up to set email alerts
|

Real time diagnostics of gas/water assisted injection moulding using integrated ultrasonic sensors

Abstract: An ultrasound sensor system has been applied to the mould of both the water and gas assisted injection moulding processes. The mould has a cavity wall mounted pressure sensor and instrumentation to monitor the injection moulding machine.Two ultrasound sensors are used to monitor the arrival of the fluid (gas or water) bubble tip through the detection of reflected ultrasound energy from the fluid polymer boundary and the fluid bubble tip velocity through the polymer melt is estimated.The polymer contact with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Ono et al made a great contribution in this area. Specifically, a high temperature ultrasonic transducer was invented and applied in microinjection molding [45], coinjection molding [46], and gas-assisted injection molding processes [47] for online polymer characterization. By installing high temperature ultrasound transducers at the nozzle location, Wu et al [48,49] revealed the flow characteristics of the polymer melt and the flow conditions at the nozzle.…”
Section: Ultrasound Ultrasound Waves Are Mechanical Wavesmentioning
confidence: 99%
“…Ono et al made a great contribution in this area. Specifically, a high temperature ultrasonic transducer was invented and applied in microinjection molding [45], coinjection molding [46], and gas-assisted injection molding processes [47] for online polymer characterization. By installing high temperature ultrasound transducers at the nozzle location, Wu et al [48,49] revealed the flow characteristics of the polymer melt and the flow conditions at the nozzle.…”
Section: Ultrasound Ultrasound Waves Are Mechanical Wavesmentioning
confidence: 99%
“…In WACIM, the thickness of the layer walls significantly affects the mechanical properties of molded products and is an important factor in judging the quality of the products . Many studies have been conducted to investigate the thickness and distribution of residual walls of the products . Kuang et al .…”
Section: Introductionmentioning
confidence: 99%
“…employed ultrasound to monitor the injection‐molding process and characterize the polymer morphology changes. Mulvaney‐Johnson et al . applied an ultrasound sensor system for real‐time diagnosis of water‐ and gas‐assisted injection molding.…”
Section: Introductionmentioning
confidence: 99%
“…Michaeli et al employed ultrasonic technology for on‐line monitoring of the polymer state during the injection molding process . Ono et al developed a high temperature ultrasonic transducer and utilized it to perform on‐line polymer characterization during microinjection molding, co‐injection molding, and gas assisted injection molding processes . Zhao et al proposed an ultrasonic method for cavity pressure analysis during the injection molding process .…”
Section: Introductionmentioning
confidence: 99%